Modulation of micrornas expression for tam phenotype reprogramming as a cancer immunotherapy approach - Neto, Carolina Ferreira (2021)
Macrophages play an important role in tumour progression and metastasis due to the plasticity expressed during activation, especially noticeable in vivo. Depending on the signals present in the tumour microenvironment (TME), macrophages can have a pro-inflammatory phenotype, known as M1 macrophages, or an anti-inflammatory phenotype, known as M2 macrophages. M1 macrophages are associated with the cancer-related inflammation common in the early stages of tumorigenesis. Later, signals from the TME can polarize macrophages towards an M2-like phenotype, referred as tumour-associated macrophages (TAMs), a pro-tumour response, which leads to tumour progression, angiogenesis, and metastasis. The presence of TAMs in the TME is normally linked to a poor prognosis for cancer patients. The activation state and, consequently, the functions of macrophages are tightly regulated by microRNAs (miRNAs). miRNAs regulate geneexpression after transcription and modulate many aspectsof the immune responses such as differentiation, proliferation, cells’ function, but also, cytokine responses. miRNAs can act either as oncogenes or as tumour suppressors, by affecting the polarization of macrophages. There are miRNAs involved both in the promotion or inhibition of macrophage activated phenotypes, besides miRNAs involved in differentiation. Alterations in miRNA expression can drive oncogenesis, tumour progression and metastasis, by contributing to the generation of TAMs. TAMs in conjunction with miRNAs are great therapeutic candidates. Therapeutically regulating miRNA levels may be linked to cancer treatment and to the regulation of the immune response. Reactivating pro-inflammatory genes in TAMs might help to promote tumour rejection. This project aims to compile a review of the literature concerning miRNA’s modulation towards cancer immunotherapy, but also to assess the effect of anticancer drugs in the expression of selected miRNAs, focusing on reprogramming TAMs phenotype.